Panel of three cytokines predicts occurrence of aGVHD after allo-HSCT: a retrospective study - Xia, Lin; Wang, Yue; Deng, Shaping; Qi, Yuqiu; Wang, Zhuo (Frontiers in Immunology, 2026)
IntroductionMany cytokines have been used as candidate biomarkers of acute graft-versus-host disease (aGVHD). Among these, the roles of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-8, IL-10, IL-17A, and IL-1β in aGVHD remain debatable, whereas IL-2, IL-12P70, IL-4, IL-5, and IFN-α are key elements in the pathological process of aGVHD. This study aimed to verify whether these 12 cytokines could serve as potential biomarkers of aGVHD in patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT).MethodsIn this retrospective study, 155 patients were stratified into control (non-aGVHD) and experimental (aGVHD) groups based on the occurrence of aGVHD. The association between cytokine levels and aGVHD occurrence was evaluated.ResultsThe expression levels of IL-5, IL-8, and IL-10 were significantly elevated in patients with aGVHD compared to those in patients without aGVHD. The results of multivariate analysis revealed that IL-5, IL-8, and IL-10 were independent risk variables for aGVHD. These three cytokines formed a composite biomarker panel with a good predictive ability for aGVHD. The panel remained an independent predictor in multivariable analysis (HR = 3.34, 95% CI: 1.66 - 6.69, P < 0.001). The composite biomarker panel demonstrated robust discriminative performance upon internal validation with 1000 bootstrap resamples.DiscussionThe composite biomarker panel comprising IL-5, IL-8, and IL-10 may serve as an important biomarker for predicting aGVHD occurrence.